THE EFFECTIVENESS OF USING CALL AND LANGUAGE LABORATORY ON IMPROVING STUDENTS LISTENING SKILL AT THE FIRST GRADE STUDENTS OF SMK TRIGUNA UTAMA - S.Pd, M.Pd, Dafitri Andri (Paradigma Lingua, 2017)
The purpose of this experimental study is to investigate: (1) whether there is any significant difference of students’ listening skill gained by the students taught using CALL; (2) whether there is any significant difference of students’ listening skill gained by the students taught using Language Laboratory; (3) whether there is any significant difference of students’ listening skill gained by the students taught using CALL and the one taught using Language Laboratory. A quantitative analysis which covered descriptive analysis statistics (mean, median, modus, maximum, minimum and standard deviation and frequency distribution), and the inferential analysis by using t-test were carried out to answer the research question of this study. To collect data, the test used the instruments: listening test which was standardized consists of pre-test and post-test. Pre-test was carried out to know that students’ listening skill of both groups was same. Post-test was done to figure out the effectiveness of treatment has been given to students. The data was counted by using t-test in SPSS for windows. The series of quantitative analysis finding indicate the improvement on students’ listening skill in both classes. It was supported by the result of dependent t-test for CALL and Language Laboratory classes where p-value = 0.000 > 0.05. In addition, the result of dependent paired t-test showed that t=0.05 which meant that H1 was accepted and H0 was rejected. In addition, this research consisted of the two independent variables (CALL and Language Laboratory) and one dependent variable (students’ listening skill